Anti-interleukin-5 antibody treatment (mepolizumab) in active eosinophilic oesophagitis: a randomised, placebo-controlled, double-blind trial. Issue 1 (13th October 2009) - Straumann, A; Conus, S; Grzonka, P; Kita, H; Kephart, G; Bussmann, C; Beglinger, C; Smith, D A; Patel, J; Byrne, M; Simon, H-U
Abstract : Objective: Eosinophilic oesophagitis (EoO) is a clinicopathological condition defined by proton pump inhibitor-refractory oesophageal symptoms combined with oesophageal eosinophilia. The pharmacodynamic effect of mepolizumab (a humanised anti-interleukin-5 monoclonal antibody) in EoO was evaluated. Methods: Eleven adults with active EoO (>20 peak eosinophil number/high power field (hpf) and dysphagia) were randomised to 750 mg of mepolizumab (n = 5) or placebo (n = 6) and received two intravenous infusions, 1 week apart. Those not in complete remission (<5 peak eosinophil number/hpf) after 8 weeks received two further doses 4 weeks apart, 1500 mg of mepolizumab or placebo. The effect of mepolizumab was assessed clinically, endoscopically, histologically, and via blood and tissue biomarkers. Results: As assessed by immunofluorescence, a marked reduction of mean oesophageal eosinophilia (p = 0.03) was seen in the mepolizumab group (−54%) compared with the placebo group (−5%) 4 weeks after initiation of treatment. No further reduction of eosinophil numbers was observed in response to the two additional infusions in either group. Mepolizumab reduced tenascin C (p = 0.033) and transforming growth factor β1 (p = 0.05) expression in the oesophageal epithelial layer 13 weeks after initiation of treatment. Clinically, limited improvement of symptoms was seen, although a trend was seen between 4 and 13 weeks after initiation of mepolizumab treatment. Mepolizumab was well tolerated. Conclusions: Mepolizumab significantly reduced eosinophil numbers in oesophageal tissues in adult patients with active EoO, and changes in the expression of molecules associated with oesophageal remodelling were reversed. Minimal clinical improvement was achieved in a subgroup of patients with EoO. Mepolizumab had an acceptable safety profile, even at the high 1500 mg dose level. Trial registration number: NCT00274703